USING THE MOMENTS OF A THICK LAYER TO MAP CONDUCTANCE AND CONDUCTIVITY FROM AIRBORNE ELECTROMAGNETIC DATA - Smith R.S.; Lee T.J. (My University, 2002)
The moments of the airborne electromagnetic impulse response have been derived for a thick horizontal layer. These moments can be written in an analytic form for the first- and second-order moments, both for the horizontal component and the vertical component. In the limiting case of a thin sheet, the horizontal component has first-, second- and third-order moments, while the vertical component has first- and second-order moments. On the other hand, the limiting case of a half space only has first-order moments for both components. The analytic expressions for the moments can be inverted analytically, so that the half space conductivity, thin-sheet conductance, and conductivity and thickness can be estimated. The images derived from the higher-order moments better identify a deeper conductor. This is consistent with the higher-order moments being more responsive to deeper material.
Keywords: AIRBORNE; ELECTROMAGNETICS; MOMENTS; CONDUCTANCE; CONDUCTIVITY